PARP inhibitors elicit a cellular senescence mediated inflammatory response in homologous recombination proficient cancer cells - Misato Kamii; Ryo Kamata; Hitoshi Saito; Gaku Yamamoto; Chiaki Mashima; Toyohiro Yamauchi; Takehiro Nakao; Yuta Sakae; Tomoko Yamamori-Morita; Kazuki Nakai; Yumi Hakozaki; Masataka Takenaka; et al. (Scientific Reports)
Abstract Poly (ADP-ribose) polymerase (PARP) inhibitors have improved the prognosis of homologous recombination deficient (HRD) ovarian cancer (OC), while effective therapeutic strategies for HR-proficient (HRP) OC still need to be established. This study investigates senescence-mediated inflammation as a novel mechanism of action for PARP inhibitors in HRP cancers. Transcriptome analyses were performed in olaparib-treated HeLa cells as a HRP model. Interferon regulatory factor-Lucia luciferase (IRF-Luc) reporter activity was assessed. The effects of PARP inhibitors on senescence-like phenotypes were assessed in seven HRP cancer cell lines, based on morphological changes, senescence-associated β-galactosidase (SA-β-GAL) activity, cellular granularity, and senescence-associated secretory phenotype (SASP)-related gene expression. Peripheral blood mononuclear cell (PBMC) migration assays were also performed with the conditioned medium in treatment with the PARP inhibitor. Transcriptome analyses revealed numbers of inflammatory cytokine- and chemokine-related pathways were significantly upregulated in olaparib-treated HeLa cells, which were confirmed by IRF-Luc reporter assays. The PARP inhibitors induced senescent phenotypes in HRP cancer cell lines: flattened and enlarged morphology, increased SA-β-GAL activity, elevated cellular granularity, and upregulated expressions of SASP-related genes (e.g., IL1B, IL6, and CXCL10). Furthermore, in vitro migration assays revealed that PARP inhibitor-treated HRP cancer cells attracted PBMCs more abundantly, suggesting the potential for recruiting immune cells to HRP cancer cells through senescence-mediated immunological activation. Our findings suggest that PARP inhibitors recruit immune cells to HRP cancer cells, potentially activating immune responses in the tumor microenvironment, providing new insights into the clinical benefits of PARP inhibitors in immunotherapy for patients with HRP OC.